Abstract MMLSE 2007 Braumann - Braumann, Carlos A. (2008)
Scientific meeting. Mathematical Models in Life Sciences & Engineering 2007 (IX Jornadas de Investigación y Fomento de la Multidisciplinaridad), Valencia, Spain, Sep 19-21, 2007. Invited inaugural conference. Review on author's results concerning stochastic differential equation models of population growth and harvesting in random environments.